The Impact of Tax Avoidance on Tax Risk: Does Good Corporate Governance Matter? - Mega Putri, Irma (GoAcademica Research & Publishing, 2024)
Tax avoidance is considered a complex issue because it has economic consequences. This study aims to determine how tax avoidance affects tax risk and how the role of corporate governance moderation variables. Data comes from the Indonesian Stock Exchange for financial reports of consumer goods companies during 2019-2023 using the purposive sampling method simple regression analysis and MRA were used to process the research data. The research results prove that tax avoidance has a significant negative impact on tax risk. The decrease in ETR as a proxy for tax avoidance will increase tax risk. In addition, the author found that in the future the effect of tax avoidance on tax risk will decrease if there is good corporate governance. This proves that tax avoidance is a risky deception for the Company in the future. Therefore, the outcome can offer managerial implications, namely encouraging shareholders and regulators to strengthen the corporate governance structure, to create public trust and protect stakeholder interests.